Perbandingan Kadar NT-proBNP Serum Pasien PGK eGFR - Made Padma Puspita; Widodo Widodo; Agus Subagio (DiscoverSys Inc., 2019)
Background: N-terminal-proBNP (NT-proBNP) is one of the most important biomarkers in diagnosing heart failure (HF). The excretion of NT-proBNP is affected by the decline of kidney function, thus the interpretation of serum levels of NT-proBNP in chronic kidney disease (CKD) patients to diagnose HF needs to be assessed carefully. Therefore, the purpose of this study is to investigated the difference between NT-proBNP levels in CKD patient with and without heart failure.Method: This observational analytic with cross-sectional study examined primary data of the serum level of NT-proBNP in predialyzed CKD patients with and without HF in outpatient clinic in Dr. Soetomo hospital, Surabaya between August and September 2018. Kidney function in predialyzed patients were classified into five stages using the Cockcroft Gault formula of estimated glomerular filtration rate (eGFR). Patients with eGFR <60mL/min/1.73m2 were included in this study. The differences between NT-proBNP levels in predialyzed CKD patients with and without heart failure were then analyzed using univariate and bivariate analysis.Results: The study population consisted of 50 predialyzed CKD patients which include 25 patients with HF and 25 patients without HF. The NT-proBNP mean in HF patients was [23,082 pg/mL (22,413)] and in patients without HF was [815 pg/mL (651)]. There was significant difference in NT-proBNP level between patients with HF and without HF (p<0,001).Conclusion: This study showed that there was significant increase in NT-proBNP level of predialyzed CKD patients with HF compare to patients without HF.